2019
DOI: 10.1111/1471-0307.12655
|View full text |Cite
|
Sign up to set email alerts
|

Performance of different microbial cultures in potentially probiotic and prebiotic yoghurts from cow and goat milks

Abstract: Lactobacillus acidophilus or Bifidobacterium animalis subsp. lactis Bb-12 and green banana pulp were used in order to obtain potentially probiotic and prebiotic yoghurts, which were compared over a 45-day storage period. Goat milk yoghurts demonstrated probiotic effects up to 45 days of storage. Cow milk yoghurts produced with B. animalis subsp. lactis Bb-12 showed a probiotic effect reduction during the storage period (1.74 log CFU/g). The type of milk affected the yoghurts' chemical and physicochemical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 45 publications
1
33
0
1
Order By: Relevance
“…Type of milk and cheese production, together with added microorganisms play an important role in sensory quality and stability during storage. It was demonstrated that probiotic cow’s milk yoghurts scored better sensory quality than goat’s milk yoghurts with added probiotic culture after 45 storage days ( 16 ). Cheese types with probiotic cultures have demonstrated improved quality and health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Type of milk and cheese production, together with added microorganisms play an important role in sensory quality and stability during storage. It was demonstrated that probiotic cow’s milk yoghurts scored better sensory quality than goat’s milk yoghurts with added probiotic culture after 45 storage days ( 16 ). Cheese types with probiotic cultures have demonstrated improved quality and health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Various formulations based on these carrier matrices are widely available in the market at present (Ranadheera et al, 2017). However, fermented dairy products such as yogurt and fermented milk are the most common and the traditional modes of delivering probiotics to humans (Mitra & Ghosh, 2020;Lucatto et al, 2020). Delivery of probiotics through carrier food products seems more efficient due to the synergistic effect among the ecapsulants and the food carrier which can provide additioonal protection to the probiotics during gastrointestinal transit (Ranadheera et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some strains may also provide texture improvements (Guimarães et al, 2020), and even mitigate toxic compounds in food products (Khorshidian et al, 2020). Probiotic microorganisms are mostly incorporated in dairy products such as yoghurts and fermented milk (Alizadeh Khaledabad et al, 2020;Lucatto et al, 2020;Sarfraz et al, 2019;Shafi et al, 2019), which is why they must be resistant to the presence of oxygen and high temperatures, conditions that are typical in food processing (Fernández et al, 2015;Motta & Gomes, 2015).…”
Section: Introductionmentioning
confidence: 99%